2017
DOI: 10.1371/journal.pgen.1006663
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Arabidopsis SC35 and SC35-like serine/arginine-rich proteins affects the transcription and splicing of a subset of genes

Abstract: Serine/arginine-rich (SR) proteins are important splicing factors which play significant roles in spliceosome assembly and splicing regulation. However, little is known regarding their biological functions in plants. Here, we analyzed the phenotypes of mutants upon depleting different subfamilies of Arabidopsis SR proteins. We found that loss of the functions of SC35 and SC35-like (SCL) proteins cause pleiotropic changes in plant morphology and development, including serrated leaves, late flowering, shorter ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 127 publications
1
101
1
Order By: Relevance
“…While a quintuple mutant in SC35 and SCL genes displays pleiotropic alterations in plant morphology and development, no phenotypic changes were observed for the other mutants, including the sr quadruple mutant that is supposedly defective in the expression of the related factors SR34, SR34a, SR34b, and SR30. However, our analysis of the T-DNA insertion line SALK_116747C in SR30, which was used by Yan et al (2017), revealed no difference in the SR30 expression pattern compared to the wild type (Supplemental Fig. S3A), suggesting that the sr quadruple mutant generated by Yan et al (2017) is, at least for SR30, not a knockout.…”
Section: Fine-tuning Sr30 Expression Via As In Development and Stressmentioning
confidence: 87%
See 2 more Smart Citations
“…While a quintuple mutant in SC35 and SCL genes displays pleiotropic alterations in plant morphology and development, no phenotypic changes were observed for the other mutants, including the sr quadruple mutant that is supposedly defective in the expression of the related factors SR34, SR34a, SR34b, and SR30. However, our analysis of the T-DNA insertion line SALK_116747C in SR30, which was used by Yan et al (2017), revealed no difference in the SR30 expression pattern compared to the wild type (Supplemental Fig. S3A), suggesting that the sr quadruple mutant generated by Yan et al (2017) is, at least for SR30, not a knockout.…”
Section: Fine-tuning Sr30 Expression Via As In Development and Stressmentioning
confidence: 87%
“…However, our analysis of the T-DNA insertion line SALK_116747C in SR30, which was used by Yan et al (2017), revealed no difference in the SR30 expression pattern compared to the wild type (Supplemental Fig. S3A), suggesting that the sr quadruple mutant generated by Yan et al (2017) is, at least for SR30, not a knockout. Besides analyzing full knockout mutants, it will be of interest to examine phenotypes of sr mutants under specific growth conditions including stress regimes.…”
Section: Fine-tuning Sr30 Expression Via As In Development and Stressmentioning
confidence: 87%
See 1 more Smart Citation
“…Having confirmed the utility of SpliSER, we also implemented a method that would allow detection of differentially spliced sites across the genome between samples. To assess the efficacy of this approach, we applied SpliSER on a previously published RNA-Seq data on quintuple mutants of the sc35-scl in Arabidopsis thaliana 25 . In this comparison, Yan et al, utilised ASD to detect 213 differentially spliced events representing 199 genes (p-value<0.05) of which 34 were detected after FDR based analysis (FDR<0.05) 25 .…”
Section: Resultsmentioning
confidence: 99%
“…An alternative approach evolved from a historical description of various types of splicing events such as intron retention, exon skipping, mutually exclusive exons and 5' and 3' alternative splice sites etc 22,23 . Several approaches including rMATS 24 , ASD 25 , SUPPA2 26 rely on quantifying splicing events. However, grouping splicing events across different genes to make inferences (e.g., increase in exon skipping or intron retention in a mutant compared to wild type) suggests biological categorization and common regulatory mechanism, which can be misleading.…”
Section: Introductionmentioning
confidence: 99%